Future changes in rice yield over Kerala using climate change scenario from high resolution global climate model projection - Stella Jes Varghese; Sajani Surendran; B Ajithkumar; Kavirajan Rajendran; Akio Kitoh (Journal of Earth System Science, 2020)

Amplified tropical Pacific rainfall variability related to background SST warming - Ning Sun; Tianjun Zhou; Xiaolong Chen; Hirokazu Endo; Akio Kitoh; Bo Wu (Climate Dynamics, 2020)
Previous studies have found that under global warming, El Niño/Southern Oscillation (ENSO)-related rainfall variability will become enhanced over the tropical central-eastern Pacific and weakened over the western Pacific. The climatological sea surface temperature (SST) warming pattern exhibits a warming center in the equatorial eastern Pacific in projections. How this pattern contributes to projected changes in ENSO-driven rainfall variability has not been fully addressed. Here, we use “time-slice” experiments to investigate the response of interannual variability in tropical Pacific rainfall in boreal winter to a warming background SST and associated physical mechanisms. A high-resolution Atmosphere General Circulation Model is driven by the detrended observational SST (1979–2003) plus a warming pattern from the coupled model under the A1B emission scenario (2075–2099). The results show that precipitation interannual variability over the tropical central-eastern Pacific will be enhanced more than the surrounding regions under warming, which is mostly contributed by a faster increase in rainfall amount during the El Niño year relative to non-El Niño years. Based on a moisture budget analysis, both the dynamic and thermodynamic components in the vertical advection of climatological specific humidity contribute to the enhancement of El Niño-induced precipitation anomalies in the tropical central-eastern Pacific where the dynamic effect is dominant. Moist static energy budget analysis further illustrates that vertical velocity is enhanced due to the increased transport of moist static energy from the lower troposphere into the middle-upper troposphere and the intensified warming effect of cloud longwave radiation caused by the increase of high cloud amount and altitude.

Future projections of Indian Summer Monsoon under multiple RCPs using a high resolution global climate model multiforcing ensemble simulations - Stella Jes Varghese; Sajani Surendran; Kavirajan Rajendran; Akio Kitoh (Climate Dynamics, 2020)

Seasonal precipitation change in the Western North Pacific and East Asia under global warming in two high-resolution AGCMs - Chao-An Chen; Huang-Hsiung Hsu; Chi-Cherng Hong; Ping-Gin Chiu; Chia-Ying Tu; Shian-Jiann Lin; Akio Kitoh (Climate Dynamics, 2019)

Monsoon rainfall over India in June and link with northwest tropical pacific - Sajani Surendran; Sulochana Gadgil; Kavirajan Rajendran; Stella Jes Varghese; Akio Kitoh (Theoretical and Applied Climatology, 2019)

East Asian climate under global warming: understanding and projection - Jianping Li; Huang-Hsiung Hsu; Wei-Chyung Wang; Kyung-Ja Ha; Tim Li; Akio Kitoh (Climate Dynamics, 2018)

Asian monsoon climate change - Understanding and prediction - Kyung-Ja Ha; June-Yi Lee; Bin Wang; Shang-Ping Xie; Akio Kitoh (Asia-Pacific Journal of Atmospheric Sciences, 2017)

West African monsoon decadal variability and surface-related forcings: second West African Monsoon Modeling and Evaluation Project Experiment (WAMME II) - Yongkang Xue; Fernando De Sales; William K.-M. Lau; Aaron Boone; Kyu-Myong Kim; Carlos R. Mechoso; Guiling Wang; Fred Kucharski; Kathleen Schiro; Masahiro Hosaka; Suosuo Li; Leonard M. Druyan; et al. (Climate Dynamics, 2016)

The seasonally varying effect of the Tibetan Plateau on Northern Hemispheric blocking frequency and amplitude - Kyung-Sook Yun; Ye-Won Seo; Kyung-Ja Ha; June-Yi Lee; Akio Kitoh (Climate Dynamics, 2016)

Effects of mountain uplift on global monsoon precipitation - June-Yi Lee; Bin Wang; Kyong-Hwan Seo; Kyung-Ja Ha; Akio Kitoh; Jian Liu (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Summer monsoon rainfall scenario over Bangladesh using a high-resolution AGCM - Md. Mizanur Rahman; M. Rafiuddin; Md. Mahbub Alam; Shoji Kusunoki; Akio Kitoh; F. Giorgi (Natural Hazards, 2013)

Future climate of the Caribbean from a super-high-resolution atmospheric general circulation model - Trevor C. Hall; Andrea M. Sealy; Tannecia S. Stephenson; Shoji Kusunoki; Michael A. Taylor; A. Anthony Chen; Akio Kitoh (Theoretical and Applied Climatology, 2013)

Future changes in tropical cyclone activity in the North Indian Ocean projected by high-resolution MRI-AGCMs - Hiroyuki Murakami; Masato Sugi; Akio Kitoh (Climate Dynamics, 2013)

Changes in climate classification and extreme climate indices from a high-resolution future projection in Korea - Kyung-Sook Yun; Ki-Young Heo; Jung-Eun Chu; Kyung-Ja Ha; Eun-Jeong Lee; Yumi Choi; Akio Kitoh (Asia-Pacific Journal of Atmospheric Sciences, 2012)

Hyperuricemia cosegregating with osteogenesis imperfecta is associated with a mutation in GPATCH8 - Hiroshi Kaneko; Hiroshi Kitoh; Tohru Matsuura; Akio Masuda; Mikako Ito; Monica Mottes; Frank Rauch; Naoki Ishiguro; Kinji Ohno (Human Genetics, 2011)

Diagnostic metrics for evaluation of annual and diurnal cycles - Bin Wang; Hyung-Jin Kim; Kazuyoshi Kikuchi; Akio Kitoh (Climate Dynamics, 2011)

Intercomparison and analyses of the climatology of the West African Monsoon in the West African Monsoon Modeling and Evaluation project (WAMME) first model intercomparison experiment - Yongkang Xue; Fernando De Sales; W. K.-M. Lau; Aaron Boone; Jinming Feng; Paul Dirmeyer; Zhichang Guo; Kyu-Myong Kim; Akio Kitoh; Vadlamani Kumar; Isabelle Poccard-Leclercq; Natalie Mahowald; et al. (Climate Dynamics, 2010)

The SST‐forced predictability of the sub‐seasonal mode over East Asia with an atmospheric general circulation model - Ki‐Young Kim; Akio Kitoh; Kyung‐Ja Ha (International Journal of Climatology, 2008)
The sea surface temperature (SST)‐forced predictability in precipitation is investigated in terms of the seasonal mean modes (SMMs) for June–July (JJ) and the sub‐seasonal mode (SSM) using the 24‐year six‐member ensembles simulation with an atmospheric general circulation model (AGCM). The SSM was defined as a 20‐day window length by an extended empirical orthogonal function (EOF) over the East Asian monsoon region. For the JJ mean rainfall, the first EOF of the model ensemble is considered to be the forced SST mode, with being an El Niño Southern Oscillation (ENSO) related pattern from the regressed SST field. The first mode of model was well correlated with the second mode of the observation in the spatial and temporal variation. In the potential predictability, the analysis of variance (ANOVA) was used for the mean mode and the SSM. The potential predictability for the SMM is improved over the north of the 30°N. Compared with JJ mean mode, the SSM has more SST‐forced variance and less internal variability. Copyright © 2008 Royal Meteorological Society

East Asian summer monsoon simulation by a 20-km mesh AGCM - Akio Kitoh; Shoji Kusunoki (Climate Dynamics, 2008)

Variability of Indian monsoon-ENSO relationship in a 1000-year MRI-CGCM2.2 simulation - Akio Kitoh (Natural Hazards, 2007)

ENSO modulation by mountain uplift - Akio Kitoh (Climate Dynamics, 2007)

Sensitivity of the central Asian climate to uplift of the Tibetan Plateau in the coupled climate model (MRI‐CGCM1) - Manabu Abe; Tetsuzo Yasunari; Akio Kitoh (Island Arc, 2005)
The relationship between the altitude of the Tibetan Plateau and climate change in central Asia was investigated through a numeric experiment using the Meteorological Research Institute (MRI) coupled atmosphere–ocean general circulation model I (MRI‐CGCM1). The results suggest that summer precipitation in central Asia decreased significantly as the Tibetan Plateau rose in height. Spring precipitation, however, increased during initial growth stages when the plateau height was up to 40% of its present‐day height, and then decreased with further plateau growth. During the Tibetan Plateau uplift, the difference between precipitation and evaporation was minimal during spring. When the plateau attained a height exceeding 60% of its present height, relatively low precipitation but high evaporation in spring led to a lower amount of ground moisture. In the case of the high plateau, sensible heat flux during summer and fall largely exceeded latent heat flux. Change was particularly significant for cases when the plateau reached 40–60% of its present‐day height. The duration of the predominant sensible heat flux became longer with the uplift of the Tibetan Plateau. The period in which latent heat exceeded sensible heat seems to have been restricted to winter and early spring. The numeric experiments suggest that a significant drying of central Asia corresponded to the period in which the Tibetan Plateau exceeded approximately half its present‐day height.

Future projections of precipitation characteristics in East Asia simulated by the MRI CGCM2 - Akio Kitoh; Masahiro Hosaka; Yukimasa Adachi; Kenji Kamiguchi (Advances in Atmospheric Sciences, 2005)